2016
DOI: 10.1088/1748-6041/11/4/045006
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin adsorption on osteoconductive hydroxyapatite and non-osteoconductiveα-alumina

Abstract: The osteoconductivity mechanism of hydroxyapatite (HAp) has not been elucidated. It is hypothesized that specific proteins adsorb on HAp, promoting its osteoconductivity. To verify this hypothesis, we compared the adsorption behavior of fibronectin (Fn) on HAp powder and on α-alumina (α-Al2O3) powder, a material with no osteoconductivity. More Fn adsorbed on α-Al2O3 than on HAp, irrespective of the Fn concentration, and there was no significant difference in the secondary structure of Fn adsorbed on HAp and α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…HAp powder (HAP-200, Taihei Chemical Industrial, Osaka, Japan) and α-Al 2O3 powder (ALO14PB, Kojundo Chemical, Saitama, Japan) were used as materials for protein adsorption. We confirmed the composition and purity of HAP-200 and ALO14PB by X-ray diffraction analysis, which established that they contained only HAp and α-Al 2O3, respectively 14) . Based on the measured surface area, 867 mg of HAp powders and 386 mg of α-Al 2O3 powders, which gave the same surface area of 3.2 m 2 , were used for adsorption of serum proteins.…”
Section: Extraction Of Rat Serum Proteins Adsorbed On Hap and α-Al2o3 Samplessupporting
confidence: 58%
See 2 more Smart Citations
“…HAp powder (HAP-200, Taihei Chemical Industrial, Osaka, Japan) and α-Al 2O3 powder (ALO14PB, Kojundo Chemical, Saitama, Japan) were used as materials for protein adsorption. We confirmed the composition and purity of HAP-200 and ALO14PB by X-ray diffraction analysis, which established that they contained only HAp and α-Al 2O3, respectively 14) . Based on the measured surface area, 867 mg of HAp powders and 386 mg of α-Al 2O3 powders, which gave the same surface area of 3.2 m 2 , were used for adsorption of serum proteins.…”
Section: Extraction Of Rat Serum Proteins Adsorbed On Hap and α-Al2o3 Samplessupporting
confidence: 58%
“…However, adsorption of bovine serum albumin led to inhibition of the attachment of RAW264.7 macrophages on α-Al 2O3 but not on the HAp surface 13) . Further, we revealed that fibronectin or laminin adsorbed on HAp enhanced the attachment and spreading of MC3T3-E1 cells; however, on α-Al 2O3, they showed no such effect [14][15][16] . These studies suggest that serum proteins display remarkably different functions depending on whether they are adsorbed on a bioceramic material.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Soaking in serum-containing medium resulted in a similar amount of Fn adsorbed on all three surfaces. The zeta potential of Fn is ¹7 mV 26) but Fn adsorption was not dependent on the surface potential of the samples. We reduced the effect of ions in each medium by assessing Fn adsorption on the samples after soaking in Fn-containing Tris-HCl solution.…”
Section: Resultsmentioning
confidence: 95%
“…One approach to resolving this dilemma is to make a composite material where the different components promote antimicrobial activity and biocompatible properties respectively. For the latter, synthetic HA is well-known to simulate the mineral properties of natural bone, and is regarded as a biocompatible and osteoconductive material [12,13]. Traditional micron scale HA has been used for some years to enhance the biocompatibility of bone implants [14].…”
Section: Introductionmentioning
confidence: 99%